IMPACT OF THE DESIGN OF DISCHARGE ELECTRODE ON THE CURRENT/VOLTAGE CHARACTERISTICS AND THE RATE OF MIGRATION IN ELECTROSTATIC PRECIPITATION (ESP) - Tahir, M. S.; Gruber, C.; Siebenhofer, M.; Saleem, M. (The Nucleus, 2020)
Efficient removal of submicronic particles is a major challenge in off-gas purification. Due to the diverse nature of chemicals produced and the chemical nature of several air born particulates (aerosols), removal by filtration and/or dry electrostatic precipitation may cause efficiency and liability problems. Problems may arise in off-gas purification of high temperature processes like off-gases from steel mills, manufacturing of multi component composite materials, thermomechanical treatment of materials and incineration processes. Rapid changes of thermodynamic states may also cause a high rate of particle formation with limited or negligible growth in size. Wet electrostatic precipitation has found specific application in this field of off-gas purification. In principle three different types of wet electrostatic precipitators are offered on the market. The tube-type electrostatic precipitator is either operated with intermittent or continuous flushing of the collecting electrodes or it is operated with rinsing by condensation. The effect of discharge electrode design on the current/voltage characteristics with specific consideration of the effect on the corona onset field intensity is being investigated in this research project.